Five-level PWM Inverter with a Single DC Power Source for DC-AC Power Conversion - Suroso Suroso; Abdullah Nur Aziz; Toshihiko Noguchi (Institute of Advanced Engineering and Science, 2017)
This paper presents a circuit configuration of five-level PWM voltage-source inverter developed from the three-level H-bridge inverter using only a single DC input power source. In the proposed five-level inverter, an auxiliary circuits working as the voltage balancing circuits of the inverter’s DC capacitors is presented. The auxiliary circuits work to keep stable DC capacitor voltages of the inverter, and also to reduce the capacitor size of the inverter. The unique point of the proposed balancing circuits is that it needs only a single voltage sensor to control the voltages of the two capacitors in the inverter. Moreover, a minimum number the inverter’s switching devices is also an important feature of the proposed inverter topology. A simple proportional integral controller is applied to control the voltage of the DC capacitors. The proposed topology is tested through computer simulation using PSIM software. Laboratory experimental tests were also conducted to verify the proposed inverter circuits. The computer simulation and experimental test results showed that the proposed balancing circuits works properly keeping stable voltages across the two DC capacitors of the inverter using only a single voltage sensor. The inverter also works well to synthesize a five-level PWM voltage waveform with sinusoidal load current.